2002
DOI: 10.1016/s1388-9842(02)00092-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum markers of collagen degradation in patients with mild to moderate dilated cardiomyopathy

Abstract: Background and aims: Left ventricular (LV) dilation and myocardial remodelling are hallmarks of heart failure in idiopathic dilated cardiomyopathy (DCM). Interstitial collagen is essential for LV integrity and function while degradation of collagen by collagenases, especially matrix-metalloproteinases (MMPs), are suggested to contribute to ventricular dilation. In the present study, serological markers of collagen metabolism were investigated. Methods and results: Serum levels of MMP-1 and its inhibitor (TIMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
80
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 33 publications
5
80
1
1
Order By: Relevance
“…Reports of changes in MMPs and TIMPs in patients with heart failure are generally consistent; reports of the ability to predict outcome are not. In heart failure, MMP1, 198 MMP2, 199,200 MMP9 199,200 and TIMP-1, 198,199,[201][202][203] but not MMP3, 199 are reported as elevated. One large study has reported that MMP9 is not elevated in patients with heart failure after adjustment for other variables.…”
mentioning
confidence: 99%
“…Reports of changes in MMPs and TIMPs in patients with heart failure are generally consistent; reports of the ability to predict outcome are not. In heart failure, MMP1, 198 MMP2, 199,200 MMP9 199,200 and TIMP-1, 198,199,[201][202][203] but not MMP3, 199 are reported as elevated. One large study has reported that MMP9 is not elevated in patients with heart failure after adjustment for other variables.…”
mentioning
confidence: 99%
“…It is known that any imbalance between a collagenase and its endogenous inhibitor can lead to changes in the ECM, causing tissue remodelling. 5,6,10,14,18,21 In the present study, MMP-9 and TIMP-1 levels and the MMP-9/TIMP-1 ratio were increased in ICM patients compared with normal control subjects, suggesting that type I collagen degradation is higher than synthesis in ischaemic myocardium. In addition, ICTP, which is the metabolite of type I collagen degradation, was also significantly increased in patients compared with normal control subjects.…”
Section: Discussionmentioning
confidence: 46%
“…13 When the myocardium is in an ischaemic state, the structure of the collagen network and the ratios of the different types of collagen appear to change. 4,6 Human and animal studies have suggested that regulating the composition of ECM can provide new insights into the prevention of cardiac remodelling in ischaemia. [14][15][16] Invasive myocardial biopsy has been the gold standard for evaluating myocardial fibrosis and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a progressive activation of MMPs results in degradation of the fibrillar collagen matrix, and can lead to increased LV wall thinning and LV enlargement [15]. Recent clinical reports have demonstrated alterations in both myocardial and circulating activities of MMPs in patients with DCM [16][17][18]. Spinale et al [18] have reported a decreased myocardial activity of the interstitial collagenase, or MMP-1, which degrades the fibrillar collagen such as collagen types I and III, as well as increased activities of gelatinases, or MMP-2 and MMP-9, in DCM.…”
Section: Discussionmentioning
confidence: 99%